THE EFFECT OF WORKLOAD AND WORK STRESS ON POLICE PERFORMANCE AT LAKA LANTAS KAMPAR POLICE - Rahmad Syamra; Zamhir Basem; Yulizar Baharuddin (STIE Bangkinang Publishing, 2023)
Research to determine the effect of workload and work stress on police performance with simulthan and partial at Laka Lantas Kampar Police. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this research were all police at the Laka Lantas Kampar Police in 2020, amounting to 39 police and all police at Laka Lantas Kampar Police were sampled so that the sampling technique in this research used a saturated census technique. Data analysis was performed using multiple linear regression models. Based on the simulthan test results, the variable of workload and work stress have a significant effect with together on the police performance at Laka Lantas Kampar Police, while based on the partial test results, the variable of workload and work stress have a significant effect with individual on the police performance at Laka Lantas Kampar Police. The closeness of the relationship that occurs between the atractiveness of workload and work stress on the police performance at Laka Lantas Kampar Police is very strong with a correlation coefficient is R of 85,5%. While contribution of workload and work stress variables to the police performance variables is equual to 73,1% while the remaining 26,9% is influenced by other variables not examined in this research.